KEGIATAN USAHA DAN PERKEMBANGAN MINIMARKET DI KABUPATEN BADUNG - Maharani, I Gusti Agung Istri; Rai Djaja, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013)
This study entitled “Business Activities and MiniMart development” is aimed to find out business activities and mini mart development. This study is using normative research. According to the method that used, it can concluded that the mini mart development is growing fast, it is caused of the human necessary and the highest of the economic development.
Keywords: Minimart, Economi, Business Activities